'Everything seems gone': Architecture and the Celtic Revival in Scotland. Issue 1 (November 2017) - MacKechnie, Aonghus
Abstract : Scotland's Celtic Revival provided new outlets for creativity, as evidenced in literature, music, painting, the plastic arts and architecture. This article discusses the architecture, particularly in the contexts which followed the defeat of Jacobitism in 1746 on Culloden's battlefield. It is argued that this revival produced a substantive architecture; more than the legion of stereotyped ringed/wheeled crosses seen throughout the country and beyond as a default monument type. It also notes the concept of revival expressed through building restorations and concludes with the memorials to the fallen of 1914–18, when wider Scottish society found value or comfort in referencing its Celtic heritage. But it is argued too that this revivalism, so far as architecture is concerned, found a narrow base and a restricted number of contexts of interest to builders, even within Gaeldom.